People mover project (control system part) - Bhuyan, Shayla Azad; Siddqui, Choudhury Tanzia; Chowdhury, Sazia Afrin; Zafarullah, Md. Kazi (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.